Báo cáo tổng hợp kết quả kiểm toán tổ chức thực hiện Chương trình phục hồi phát triển kinh tế - xã hội - Kiểm toán nhà nước (2024)
Toàn văn Báo cáo tổng hợp kết quả kiểm toán tổ chức thực hiện Chương trình phục hồi phát triển kinh tế - xã hội.